6.138 Problems 13701 to 13800

Table 6.275: Main lookup table sequentially arranged

#

ODE

Mathematica

Maple

13701

\[ {}x^{\prime \prime }+\left (5 x^{4}-6 x^{2}\right ) x^{\prime }+x^{3} = 0 \]

13702

\[ {}x^{\prime \prime }+\left (x^{2}+1\right ) x^{\prime }+x^{3} = 0 \]

13703

\[ {}[x^{\prime }\left (t \right ) = x \left (t \right )-x \left (t \right )^{2}, y^{\prime }\left (t \right ) = 2 y \left (t \right )-y \left (t \right )^{2}] \]

13704

\[ {}x^{\prime } = \sin \left (t \right )+\cos \left (t \right ) \]

13705

\[ {}y^{\prime } = \frac {1}{x^{2}-1} \]

13706

\[ {}u^{\prime } = 4 t \ln \left (t \right ) \]

13707

\[ {}z^{\prime } = x \,{\mathrm e}^{-2 x} \]

13708

\[ {}T^{\prime } = {\mathrm e}^{-t} \sin \left (2 t \right ) \]

13709

\[ {}x^{\prime } = \sec \left (t \right )^{2} \]

13710

\[ {}y^{\prime } = x -\frac {1}{3} x^{3} \]

13711

\[ {}x^{\prime } = 2 \sin \left (t \right )^{2} \]

13712

\[ {}x V^{\prime } = x^{2}+1 \]

13713

\[ {}x^{\prime } {\mathrm e}^{3 t}+3 x \,{\mathrm e}^{3 t} = {\mathrm e}^{-t} \]

13714

\[ {}x^{\prime } = -x+1 \]

13715

\[ {}x^{\prime } = x \left (2-x\right ) \]

13716

\[ {}x^{\prime } = \left (1+x\right ) \left (2-x\right ) \sin \left (x\right ) \]

13717

\[ {}x^{\prime } = -x \left (-x+1\right ) \left (2-x\right ) \]

13718

\[ {}x^{\prime } = x^{2}-x^{4} \]

13719

\[ {}x^{\prime } = t^{3} \left (-x+1\right ) \]

13720

\[ {}y^{\prime } = \left (1+y^{2}\right ) \tan \left (x \right ) \]

13721

\[ {}x^{\prime } = t^{2} x \]

13722

\[ {}x^{\prime } = -x^{2} \]

13723

\[ {}y^{\prime } = {\mathrm e}^{-t^{2}} y^{2} \]

13724

\[ {}x^{\prime }+p x = q \]

13725

\[ {}x y^{\prime } = k y \]

13726

\[ {}i^{\prime } = p \left (t \right ) i \]

13727

\[ {}x^{\prime } = \lambda x \]

13728

\[ {}m v^{\prime } = -m g +k v^{2} \]

13729

\[ {}x^{\prime } = k x-x^{2} \]

13730

\[ {}x^{\prime } = -x \left (k^{2}+x^{2}\right ) \]

13731

\[ {}y^{\prime }+\frac {y}{x} = x^{2} \]

13732

\[ {}x^{\prime }+t x = 4 t \]

13733

\[ {}z^{\prime } = z \tan \left (y \right )+\sin \left (y \right ) \]

13734

\[ {}y^{\prime }+{\mathrm e}^{-x} y = 1 \]

13735

\[ {}x^{\prime }+x \tanh \left (t \right ) = 3 \]

13736

\[ {}y^{\prime }+2 y \cot \left (x \right ) = 5 \]

13737

\[ {}x^{\prime }+5 x = t \]

13738

\[ {}x^{\prime }+\left (a +\frac {1}{t}\right ) x = b \]

13739

\[ {}T^{\prime } = -k \left (T-\mu -a \cos \left (\omega \left (t -\phi \right )\right )\right ) \]

13740

\[ {}2 x y-\sec \left (x \right )^{2}+\left (x^{2}+2 y\right ) y^{\prime } = 0 \]

13741

\[ {}1+y \,{\mathrm e}^{x}+x \,{\mathrm e}^{x} y+\left (x \,{\mathrm e}^{x}+2\right ) y^{\prime } = 0 \]

13742

\[ {}\left (x \cos \left (y\right )+\cos \left (x \right )\right ) y^{\prime }+\sin \left (y\right )-y \sin \left (x \right ) = 0 \]

13743

\[ {}{\mathrm e}^{x} \sin \left (y\right )+y+\left ({\mathrm e}^{x} \cos \left (y\right )+x +{\mathrm e}^{y}\right ) y^{\prime } = 0 \]

13744

\[ {}{\mathrm e}^{-y} \sec \left (x \right )+2 \cos \left (x \right )-{\mathrm e}^{-y} y^{\prime } = 0 \]

13745

\[ {}V^{\prime }\left (x \right )+2 y y^{\prime } = 0 \]

13746

\[ {}\left (\frac {1}{y}-a \right ) y^{\prime }+\frac {2}{x}-b = 0 \]

13747

\[ {}x y+y^{2}+x^{2}-x^{2} y^{\prime } = 0 \]

13748

\[ {}x^{\prime } = \frac {x^{2}+t \sqrt {t^{2}+x^{2}}}{t x} \]

13749

\[ {}x^{\prime } = k x-x^{2} \]

13750

\[ {}x^{\prime \prime }-3 x^{\prime }+2 x = 0 \]

13751

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 0 \]

13752

\[ {}z^{\prime \prime }-4 z^{\prime }+13 z = 0 \]

13753

\[ {}y^{\prime \prime }+y^{\prime }-6 y = 0 \]

13754

\[ {}y^{\prime \prime }-4 y^{\prime } = 0 \]

13755

\[ {}\theta ^{\prime \prime }+4 \theta = 0 \]

13756

\[ {}y^{\prime \prime }+2 y^{\prime }+10 y = 0 \]

13757

\[ {}2 z^{\prime \prime }+7 z^{\prime }-4 z = 0 \]

13758

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 0 \]

13759

\[ {}x^{\prime \prime }+6 x^{\prime }+10 x = 0 \]

13760

\[ {}4 x^{\prime \prime }-20 x^{\prime }+21 x = 0 \]

13761

\[ {}y^{\prime \prime }+y^{\prime }-2 y = 0 \]

13762

\[ {}y^{\prime \prime }-4 y = 0 \]

13763

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = 0 \]

13764

\[ {}y^{\prime \prime }+\omega ^{2} y = 0 \]

13765

\[ {}x^{\prime \prime }-4 x = t^{2} \]

13766

\[ {}x^{\prime \prime }-4 x^{\prime } = t^{2} \]

13767

\[ {}x^{\prime \prime }+x^{\prime }-2 x = 3 \,{\mathrm e}^{-t} \]

13768

\[ {}x^{\prime \prime }+x^{\prime }-2 x = {\mathrm e}^{t} \]

13769

\[ {}x^{\prime \prime }+2 x^{\prime }+x = {\mathrm e}^{-t} \]

13770

\[ {}x^{\prime \prime }+\omega ^{2} x = \sin \left (\alpha t \right ) \]

13771

\[ {}x^{\prime \prime }+\omega ^{2} x = \sin \left (\omega t \right ) \]

13772

\[ {}x^{\prime \prime }+2 x^{\prime }+10 x = {\mathrm e}^{-t} \]

13773

\[ {}x^{\prime \prime }+2 x^{\prime }+10 x = {\mathrm e}^{-t} \cos \left (3 t \right ) \]

13774

\[ {}x^{\prime \prime }+6 x^{\prime }+10 x = {\mathrm e}^{-2 t} \cos \left (t \right ) \]

13775

\[ {}x^{\prime \prime }+4 x^{\prime }+4 x = {\mathrm e}^{2 t} \]

13776

\[ {}x^{\prime \prime }+x^{\prime }-2 x = 12 \,{\mathrm e}^{-t}-6 \,{\mathrm e}^{t} \]

13777

\[ {}x^{\prime \prime }+4 x = 289 t \,{\mathrm e}^{t} \sin \left (2 t \right ) \]

13778

\[ {}x^{\prime \prime }+\omega ^{2} x = \cos \left (\alpha t \right ) \]

13779

\[ {}x^{\prime \prime }+\omega ^{2} x = \cos \left (\omega t \right ) \]

13780

\[ {}x^{\prime \prime \prime }-6 x^{\prime \prime }+11 x^{\prime }-6 x = {\mathrm e}^{-t} \]

13781

\[ {}y^{\prime \prime \prime }-3 y^{\prime \prime }+2 y = \sin \left (x \right ) \]

13782

\[ {}x^{\prime \prime \prime \prime }-4 x^{\prime \prime \prime }+8 x^{\prime \prime }-8 x^{\prime }+4 x = \sin \left (t \right ) \]

13783

\[ {}x^{\prime \prime \prime \prime }-5 x^{\prime \prime }+4 x = {\mathrm e}^{t} \]

13784

\[ {}t^{2} y^{\prime \prime }-\left (t^{2}+2 t \right ) y^{\prime }+\left (2+t \right ) y = 0 \]

13785

\[ {}\left (x -1\right ) y^{\prime \prime }-x y^{\prime }+y = 0 \]

13786

\[ {}\left (\cos \left (t \right ) t -\sin \left (t \right )\right ) x^{\prime \prime }-x^{\prime } t \sin \left (t \right )-x \sin \left (t \right ) = 0 \]

13787

\[ {}\left (-t^{2}+t \right ) x^{\prime \prime }+\left (-t^{2}+2\right ) x^{\prime }+\left (2-t \right ) x = 0 \]

13788

\[ {}y^{\prime \prime }-x y^{\prime }+y = 0 \]

13789

\[ {}\tan \left (t \right ) x^{\prime \prime }-3 x^{\prime }+\left (\tan \left (t \right )+3 \cot \left (t \right )\right ) x = 0 \]

13790

\[ {}y^{\prime \prime }-y^{\prime }-6 y = {\mathrm e}^{x} \]

13791

\[ {}x^{\prime \prime }-x = \frac {1}{t} \]

13792

\[ {}y^{\prime \prime }+4 y = \cot \left (2 x \right ) \]

13793

\[ {}t^{2} x^{\prime \prime }-2 x = t^{3} \]

13794

\[ {}x^{\prime \prime }-4 x^{\prime } = \tan \left (t \right ) \]

13795

\[ {}\left (\tan \left (x \right )^{2}-1\right ) y^{\prime \prime }-4 \tan \left (x \right )^{3} y^{\prime }+2 y \sec \left (x \right )^{4} = \left (\tan \left (x \right )^{2}-1\right ) \left (1-2 \sin \left (x \right )^{2}\right ) \]

13796

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 0 \]

13797

\[ {}4 x^{2} y^{\prime \prime }+y = 0 \]

13798

\[ {}t^{2} x^{\prime \prime }-5 t x^{\prime }+10 x = 0 \]

13799

\[ {}t^{2} x^{\prime \prime }+t x^{\prime }-x = 0 \]

13800

\[ {}x^{2} z^{\prime \prime }+3 x z^{\prime }+4 z = 0 \]